СИСТЕМА ЕЛЕКТРОЖИВЛЕННЯ ЕЛЕКТРОМАГНІТНОГО ПЕРЕМІШУВАЧА РІДКОГО МЕТАЛУ З ПОЧЕРГОВОЮ ДІЄЮ ПУЛЬСУЮЧОГО ТА БІЖУЧОГО МАГНІТНИХ ПОЛІВ - Гориславець, Ю.М.; Глухенький, О.І.; Бондар, О.І. (Інститут електродинаміки Національної академії наук України, 2019)
Power supply system of liquid metal electromagnetic stirrer with alternating periodic force action of pulsing and traveling magnetic fields have been proposed, that includes two load balancing and reactive power compensative devices (LBRPCD), allowing to compensate reactive power and to balance power supply network currents in both operation modes of stirrer. Switching of power supply modes and LBRPCD elements in this system performed by electromagnetic contactors. For each power supply mode (single phase and double phase) electromagnetic parameters of stirrer and parameters of LBRPCD elements have been determined. Stationary and time dependent simulations for system have been made. It is shown, that such system allows significantly decrease and uniformly distribute currents in power supply network in both stirrer operation modes. For decreasing of starting currents during switching utilizing of special electromagnetic contactors have been proposed, which are used for switching of capacitor banks. References 11, figures 5, table.